2011
DOI: 10.1002/eji.201141798
|View full text |Cite
|
Sign up to set email alerts
|

Half of the T‐cell repertoire combinatorial diversity is genetically determined in humans and humanized mice

Abstract: In humanized mice, the T-cell repertoire is derived from genetically identical human progenitors in distinct animals. Thus, careful comparison of the T-cell repertoires of humanized mice with those of humans may reveal the contribution of genetic determinism on T-cell repertoire formation. Here, we performed a comprehensive assessment of the distribution of V-J combinations of the human b chain of the T-cell receptor (hTRBV) in NOD.SCID.cc À/À (NSG) humanized mice. We observed that numerous V-J combinations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…the HLA-background of a host and thymic selection [63][65], or the likelyhood of certain VDJ-recombinations [65][68]. Even though the T-cell pool might vary in every individual as a result of such influences, we found that T-cells have a preference for certain amino acids (see Supplemental Table S1, the immunogenicity model).…”
Section: Discussionmentioning
confidence: 73%
“…the HLA-background of a host and thymic selection [63][65], or the likelyhood of certain VDJ-recombinations [65][68]. Even though the T-cell pool might vary in every individual as a result of such influences, we found that T-cells have a preference for certain amino acids (see Supplemental Table S1, the immunogenicity model).…”
Section: Discussionmentioning
confidence: 73%
“…Marodon et al reported that V-J combination distribution of human T cells is already present before TCR-MHC selection in the thymus of NSG mice [15]. In addition, Pham et al reported a similar distribution of human T cell receptor β chain families in the thymus of NSG mice and in human thymus, suggesting the selection of functional human T cells reconstituted in these mice [45]. In addition, some thymic selection of human T cells occurs on mouse MHC, as evidenced by a slightly increased weak proliferation of human T cells toward mismatched mouse dendritic cells as compared with that toward host ones [8].…”
Section: Discussionmentioning
confidence: 99%
“…In collaboration with ImmunID, we have proposed a novel strategy for statistical modeling of T lymphocyte repertoire data obtained in humans and humanized mice. With this model, we revealed that half of the human TRB repertoire, in terms of proportion of TRBV-TRBJ combinations, is genetically determined, the other half occurring stochastically (182). In addition, the biotechnology company “Adaptive” and the “Repertoire 10K (R10K) Project” have been recently founded by researchers respectively from the Fred Hutchinson Cancer Research Center (Seattle and Washington) and the HudsonAlpha Institute (Huntsville).…”
Section: Statistical Analysis and Modeling Of Immune Repertoire Datamentioning
confidence: 99%